Pengaruh Mutasi Dan Beban Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Bank BRI Cabang Baturaja (Persero) TBK - Noviansyah Noviansyah; Ervin Mardalena (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
This study aims to determine the effect of mutations and workloads on employee performance at PT. Bank BRI Cabang Baturaja (Persero) Tbk. The data used are primary data through questionnaire distribution. The data analysis technique used is multiple linear regression. Based on the results of the analysis, mutations and workloads partially affect the work performance of employees of PT. Bank BRI Cabang Baturaja (Persero) Tbk. The coefficient of the F-count value is 304,780 which is greater than the F-table value of 3.18, this means that Fcount> Ftable so that it can be concluded that mutations and workloads simultaneously influence the work performance of PT. Bank BRI Cabang Baturaja (Persero) Tbk. The value of R Square is 0.923, it can be seen that the percentage of the contribution of the influence of mutation and workload variables on the ups and downs of the dependent variable, namely employee work performance of 92.3% while the remaining 7.7% is determined by other variables not included in this research model such as ability and motivation factors